Transition-Metal-Free Method for the Synthesis of Benzo[b]thiophenes from o-Halovinylbenzenes and K2S via Direct SNAr-Type Reaction, Cyclization, and Dehydrogenation Process - Zhang, Xiaoyun; Zeng, Weilan; Yang, Yuan; Huang, Hui; Liang, Yun (Synlett, 2013)
A new, highly efficient procedure for the synthesis of benzothiophenes from easily available o-halovinylbenzenes and potassium sulfide has been developed. The reaction tolerated a wide range of functionalities, and various 2-substituted benzo[b]thiophenes are provided in the high yields in the absence of a transition-metal catalyst.
Keywords: transition-metal-free; benzo[b]thiophenes; o-halovinylbenzenes; direct SNAr-type reaction; cyclization; dehydrogenation process